2013
DOI: 10.1371/journal.pone.0054323
|View full text |Cite
|
Sign up to set email alerts
|

Accommodating Species Climate-Forced Dispersal and Uncertainties in Spatial Conservation Planning

Abstract: Spatial conservation prioritization should seek to anticipate climate change impacts on biodiversity and to mitigate these impacts through the development of dynamic conservation plans. Here, we defined spatial priorities for the conservation of amphibians inhabiting the Atlantic Forest Biodiversity Hotspot that overcome the likely impacts of climate change on the distribution of this imperiled fauna. First, we built ecological niche models (ENMs) for 431 amphibian species both for current time and for the mid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(57 citation statements)
references
References 63 publications
4
52
0
1
Order By: Relevance
“…Models of future distribution for other bee species also show the loss of suitable areas in future climate change scenarios (Giannini et al 2012). Climate change in the next 50 years is pointed out as a major factor in forecasts of distribution range changes for Atlantic forest trees (Colombo and Joly 2010), amphibians (Lemes and Loyola 2013) and marsupials . For South American moths, climate change will force range shifts and reduce the conservation effectiveness of some protected areas, even leading 4 % of all analysed species to extinction (Ferro et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Models of future distribution for other bee species also show the loss of suitable areas in future climate change scenarios (Giannini et al 2012). Climate change in the next 50 years is pointed out as a major factor in forecasts of distribution range changes for Atlantic forest trees (Colombo and Joly 2010), amphibians (Lemes and Loyola 2013) and marsupials . For South American moths, climate change will force range shifts and reduce the conservation effectiveness of some protected areas, even leading 4 % of all analysed species to extinction (Ferro et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This leads us to question whether its disappearance in the northern limit of its distribution in southern Brazil was caused only by habitat loss or if climate change may have also played an important role in the species disappearance from its northernmost occurrence limit in Brazil. In South America, range shifts and species losses caused by climate change have been predicted for different groups: Atlantic forest trees (Colombo and Joly 2010), amphibians (Lemes and Loyola 2013), marsupials ) and moths (Ferro et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Between these two extremes, there are other areas for research and with high conservation value such as the Atlantic rainforest, in Brazil. While a great portion of the Atlantic rainforest is currently covered by pasture and agriculture (Hansen et al., ), most priority research areas identified within this region are located in the Serra Do Mar forest, which is currently relatively well preserved and the focus of important conservation efforts (Alves‐Pinto et al., ; Lemes & Loyola, ; Loyola, Lemes, Brum, Provete, & Duarte, ; Zwiener et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The criteria for choosing sites for protection should be based on maximizing the representation of biodiversity (Coll et al, 2010), including phylogenetic and functional diversity (Mouillot et al, 2011) and minimizing the anthropogenic pressures that jeopardize biodiversity (Coll et al, 2012). Connectivity is one of these processes as it is essential to ensure population stability and persistence (Armsworth, 2002;Hastings & Botsford, 2006b) and justifies the need for further research aimed at better characterizing current patterns of connectivity and predicting their future evolution (Mumby et al, 2011;Lemes & Loyola, 2013). Connectivity is one of these processes as it is essential to ensure population stability and persistence (Armsworth, 2002;Hastings & Botsford, 2006b) and justifies the need for further research aimed at better characterizing current patterns of connectivity and predicting their future evolution (Mumby et al, 2011;Lemes & Loyola, 2013).…”
Section: Implications For Conservation and Managementmentioning
confidence: 99%